Factors Related To Compliance With Hand Hygiene Implementation Among Health Care Workers - Siringoringo, Dumaris; Reni Aprinawaty Sirait; Delita Br. Panjaitan (JURNAL KESMAS DAN GIZI (JKG), 2025)
Background: The implementation of hand hygiene (HH) is an essential aspect of healthcare management, influencing the health of both healthcare workers and the general public. Objective: This study aims to identify the factors associated with compliance in the implementation of hand hygiene among healthcare workers. Research Method: This research is a quantitative study using a cross-sectional design, conducted at Puskesmas Sialang, Bangun Purba District, Deli Serdang Regency. Results: The analysis showed that several factors had a significant relationship with hand hygiene compliance among healthcare workers, including knowledge (p-value = 0.010), attitude (p-value = 0.022), availability of facilities (p-value = 0.009), and supervision by the Infection Prevention and Control (IPC) team (p-value = 0.000). Conclusion: There is a significant influence of knowledge, attitude, facility availability, and IPC team supervision on hand hygiene compliance among healthcare workers at Puskesmas Sialang. Therefore, it is recommended to conduct awareness campaigns on hand hygiene and the associated infection risks, establish a reward and recognition system for healthcare workers who consistently practice proper hand hygiene, ensure the availability of hand hygiene facilities in easily accessible locations for healthcare workers, and enhance communication between the IPC team and healthcare workers regarding hand hygiene practices.